PERILAKU KEAGAMAAN ISLAM PADA ANAK USIA DINI - FAUZIA, SITI NAILA (Program Studi Magister Pendidikan Anak Usia Dini, 2015)
Abstract: The purpose of this study to describe the behavior of the Islamic religion in the early childhood kindergarten Sunnah gem Banda Aceh. This study is a qualitative research with phenomenological kind. Analysis of the data using the model of Miles and Huberman. Data were obtained from observations, interviews, and documentation. The results showed that (1) The behavior of Islamic religious in children include: children's understanding of the teachings of Islam, children being kind to fellow creatures of God, and the children skilled in worship, (2) The process of education, among others: use the curriculum in 2013, the flagship program is Tahfidzul quran. (3) The role of teachers in shaping the behavior of Islamic religious in children, (4) the support of parents in shaping the behavior of Islamic religious in children is a lack of support at home, and the cooperation that exists between parents and the school, (5) The success of TK gem Sunnah in Islamic form of religious behavior in children is shown in behavioral changes experienced by children, and the public trust in the school. Keywords: Formation, Religious Behavior, Islamic, Early Childhood